Review of the free-living Nematode (Nematoda) fauna of Lake Baikal - Naumova, Tatyana V.; Gagarin, Vladimir G. (Zootaxa, 2019)
A complete list of free-living nematodes found in Lake Baikal is presented. A total of 112 species of roundworms from 32 genera, 16 families and 8 orders are listed. The locations and depths of nematode finds in Baikal are indicated, information on their distribution is summarized, and zoogeographical characteristics for each species are given.